Investigation of annular free jet flows with various diameter ratios - Celik, Nevin; Bayazit, Yilmaz (My University, 2011)
In present study, a detailed investigation of an annular jet issuing into the ambient air has been reported both numerically and experimentally. The numerical simulation was performed by making use of the CFX software package which discretizes the solution domain into quadrilateral elements. Effects of the diameter ratio of the annular pipe d/D (0, 0.105, 0.35 and 0.55) and Reynolds number Re (10000, 20000 and 50000) on the mean velocities of the jet were investigated numerically. For validation of the numerical solution, some experiments were performed considering the parametric values d/D = 0.55, d/D = 0 and Re = 20000. The results are presented with normalized mean velocities u/U. The axial and radial velocities for varied diameter ratios are exhibited with graphs. New correlations are found for axial velocity distributions. Finally, it is found that the axial distance x/D = 5 is the critical point for annular jets. The effect of diameter ratio is strongly felt at the downstream axial distance x/D < 5. The effects of the diameter ratio disappeared with decreasing downstream distance x/D > 5. At sufficient downstream distances, the width of the jet was found to be independent of both the geometrical parameters and the Reynolds number. In addition, experimental results have a good agreement with numerical results.
2011 AIChE Annual Meeting, 11AIChE -- 16 October 2011 through 21 October 2011 -- Minneapolis, MN -- 88259
Keywords: Computer simulation; Reynolds number; Ambient air; Annular jets; Annular pipe; Axial distance; Axial-velocity distribution; CFX software package; Critical points; Diameter ratio; Free jets; Geometrical parameters; Mean velocities; New correlations; Numerical results; Numerical solution; Quadrilateral elements; Radial velocity; Velocity distribution